Human thelaziasis in Bangladesh - Hossain, MI; Hossain, MA; Nahar, L; Hossain, MM; Mondal, AS; Alim, MA; Mahmud, MC; Islam, A (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):128-130 The abstract of this article is available on the PubMed website